A influência da espessura da férula na resistência à fratura de dentes restaurados com diferentes pinos intrarradiculares - Fontana, Patrícia Eliana (2017)
The maintenance of the remaining coronary structure is fundamental for the prognosis of restorative treatment, and the ferrule effect is an extremely important factor, which influences the clinical outcome of teeth with endodontic treatment. The impact of ferrule thickness on fracture resistance of endodontically treated teeth remains controversial, as there are no studies to date. The objective of this study was to investigate the influence of ferrule thickness on fracture resistance after mechanical cycling and failure pattern of teeth restored with different intraradicular posts subjected to the fracture load test. One hundred and twenty bovine incisor teeth were randomized into six study groups, based on the intraradicular post used (fiber post or cast post and core) and the presence and thickness of the ferrule (without ferrule, presence of 0.5 mm or 1 mm thick ferrule, keeping unaltered 2 mm in ferrule height). Full metal crowns and the root posts were adhesively cemented. The samples were subjected to mechanical cycling (37°C, 45°, 130 N, 2.2 Hz, and 2 x 106 pulses). Afterwards, they were subjected to the fracture load test at a speed of 0.5 mm/min and a 45° slope until failure occurred. The failures were classified as favorable and unfavorable. The fracture resistance data were analyzed with 2-factor ANOVA and Tukey's test. The Mann-Whitney test and Chi-square test were used to analyze the pattern of failure. Of all the specimens, 96.7% survived the mechanical cycling. The group with cast post and core and 1 mm ferrule thickness (CPC1) presented a greater resistance to fracture that the group with cast post and core but without ferrule (CPC, p=0.001). Furthermore, varying ferrule thickness were associated with different failure patterns. Thus, ferrule thickness should be considered when choosing different intraradicular posts, looking for the less occurrence of unfavorable failures.